Strategi Peningkatan Volume Penjualan UMKM Keripik Pisang Definas di Era Pandemi Covid-19 - Rahma Ulfa Maghfiroh (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2022)
The MSMEs of definas banana chips have to be able to survive and compete during the COVID-19 pandemic. This study aims to identify the implementation of the 4P marketing mix in an effort to increase sales volume of Definas banana chips during the covid-19 pandemic, as well as analyze effective and efficient marketing strategies to be able to compete with competitors. The method uses descriptive qualitative through observation, document study, and in-depth interviews with business actors and several consumers of Definas banana chips. The results showed that the marketing strategy in the form of a marketing mix consisting of product, price, place and promotion carried out by Definas banana chips was able to survive the covid-19 pandemic. There are still several strategies that must be improved related to products and promotions in order to increase the competitiveness of Definas banana chips products.